An examination of the validity of criteria for evaluating throwing techniques, with focus on back throw and full hip throw - Yabune, T. (Association for the Scientific Studies on Judo, Kodokan, 2019)
A method for quantifiably evaluating judo throws observed from the back was created by the author in 2009, but the validity of this quantifiable scoring standard has not yet been confirmed. A good throw technique is certain to result in greater destabilization. If the degree of destabilization of the "uke" (partner) can be quantified and the score analyzed in relation to the score obtained using the author`s previously developed evaluation criteria, the evaluation criteria can be validated. Keeping this in mind, an experiment was first conducted to simply measure the uke`s degree of destabilization by specifying body position and the specific scenario. The angle of hip flexion was thought to be suitable for determining the degree of destabilization, and the appropriate scenario for determining this was thought to be the instant at which the uke comes into contact with the mock assailant`s back.108 test moves filmed during classes at KK University during the 2015 academic year were analyzed to study the correlation between scores for back throw or full hip throw and the angle of hip flexion. A strong positive correlation (correlation coefficient = 0.075, p<0.01) was noted for both variables, confirming the validity of the evaluation criteria.